A persistência da memória no programa de reabilitação: proposta de uma escola técnica no porto de Roterdão - Rita Sofia Curopos Fonseca Cunha (2016)
The proposal presented in this master thesis focuses on the restoration of two industrial buildingslocated in Rotterdam's port. The influences of history, culture and memory, of both the city and thecountry, where used as information sources for the renovation of these storage buildings.One of the main goals is to look for an answer through the study of history of the port of Rotterdamand its evolution, bearing in mind how it influenced the development of the city. Further, the dockof Merwe-Vierhaven is analyzed with a practical purpose, by means of understanding the developmentof this port area as well as the problems which it currently faces. Consequently, through this study wecan propose an intervention that comprises both architecture and urban renewal.Moreover, given that Rotterdam is a port city, it becomes imperative to analyze several theorieson the construction of waterfront cities, and how could these theories be helpful in the transformation ofthis harbor.T he new program is a technical carpentry school with a new waterbus stop, therefore it incorporatesthe surrounding public space into the project, while simultaneously creating a new public access.